The urban forest : cultivating green infrastructure for people and the environment - Pearlmutter, David; Calfapietra, Carlo; Samson, Roeland; O'Brien, Liz; Ostoić, Silvija Krajter; Sanesi, Giovanni; Amo, Rocío Alonso del (Springer, 2017)
This book focuses on urban "green infrastructure"? the interconnected web of vegetated spaces like street trees, parks and peri-urban forests that provide essential ecosystem services in cities. The green infrastructure approach embodies the idea that these services, such as storm-water runoff control, pollutant filtration and amenities for outdoor recreation, are just as vital for a modern city as those provided by any other type of infrastructure. Ensuring that these ecosystem services are indeed delivered in an equitable and sustainable way requires knowledge of the physical attributes of trees and urban green spaces, tools for coping with the complex social and cultural dynamics, and an understanding of how these factors can be integrated in better governance practices. By conveying the findings and recommendations of COST Action FP1204 GreenInUrbs, this volume summarizes the collaborative efforts of researchers and practitioners from across Europe to address these challenges.
Includes index.
Keywords: Urban forestry.; City planning.; Trees in cities.; elektronické knihy; electronic books